A formal anti-Markovnikov hydroamination of allylic alcohols via tandem oxidation/1, 4-conjugate addition/1, 2-reduction using a Ru catalyst. Issue 35 (31st March 2015) - Nakamura, Yushi; Ohta, Tetsuo; Oe, Yohei
Abstract : A formal Ru-catalyzed anti -Markovnikov hydroamination of allylic alcohols via tandem oxidation/1, 4-conjugate addition/1, 2-reduction was developed. Abstract : A formal anti -Markovnikov hydroamination of allylic alcohols using a Ru catalyst via tandem oxidation/1, 4-conjugate addition/1, 2-reduction was developed. Thus, the reaction of allylic alcohols with amines was performed in the presence of the catalyst generated from RuClH(CO)(PPh3 )3 and 2, 6-bis( n -butyliminomethyl)pyridine in situ to afford the corresponding γ-amino alcohols efficiently.